Rapid test for identification of heat-labile enterotoxin-producing Escherichia coli colonies. - Finkelstein, R A (1983)
A latex particle agglutination test is described which is suitable for the recognition of heat-labile enterotoxin-producing colonies of Escherichia coli immediately after primary culture on a variety of commonly used enteric diagnostic media. The test is simple and economical to perform, and the results are available in minutes.